The Role of FDI in Strengthening Regional and Global Economic Integration: Evidence from Kazakhstan and Kyrgyzstan (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the dynamics of Foreign Direct Investment (FDI) in Kazakhstan and Kyrgyzstan, focusing on their roles in fostering regional and global economic integration. Drawing on data from 1991 to 2024, the study highlights how Kazakhstan’s resource-driven economy and proactive investment policies have positioned it as the leading FDI destination in Central Asia, attracting over USD 370 billion since independence. The research also analyzes Kyrgyzstan’s recent recovery in FDI inflows, reaching USD 845 million in 2023 (3.51% of GDP), after periods of volatility caused by global and domestic factors. The findings reveal that Kazakhstan’s strategic initiatives such as participation in the Eurasian Economic Union (EAEU), the Belt and Road Initiative (BRI), and WTO membership have significantly enhanced its investment climate. Meanwhile, Kyrgyzstan’s growing engagement in projects like CASA-1000 and the China–Kyrgyzstan–Uzbekistan railway demonstrates its emerging role in regional connectivity and trade facilitation. Despite differences in scale and structure, both countries use FDI as a mechanism for economic modernization, infrastructure development, and regional integration. The paper concludes that maintaining political stability, improving governance, and diversifying investment sectors remain crucial for sustaining long-term FDI-led growth across Central Asia.